Afyonkarahisar ilinde ruminant abort vakalarında pestivirusların (BDV ve BVDV) rolleri - Şevik, Murat (My University, 2018)
Pestiviruslar ruminantlarda abortlara neden olan önemli viral ajanlardır. Bu çalışmada, ruminant abort vakalarında Border Disease Virus (BDV) ve Bovine Viral Diarrhoea Virus (BVDV)’un rolleri araştırılmıştır. Abort olmuş fötus doku örnekleri 101 hayvandan (74’ü koyun fötusu, 27’si sığır fötus), her biri epidemiyolojik olarak farklı çiftliklerden, Ocak 2016 ve Aralık 2017 ayları arasında Afyonkarahisar ilinden toplanmıştır. BDV ve BVDV RNA’sının tespiti için tek adımlı real-time dubleks RT-PCR yöntemi kullanılmıştır. Sahadan izole edilen pestivirus’ların genetik karakterizasyonu 5' translate olmayan bölge sonunun (5' UTR) sekansı ile gerçekleştirilmiştir. BDV RNA’sı, 74 aborte koyun fötusunun 9 (%12.16)’unda, BVDV RNA’sı ise 27 sığır fötusunun 6 (%22.2)’sında tespit edilmiştir. 5' UTR bölgesinin filogenetik analizi bu çalışmada izole edilen BDV izolatlarının BDV-7 genotipine, BVDV izolatlarının ise BVDV-1 genotipine ait olduğunu göstermiştir. Bu çalışmanın sonuçları, pestivirus enfeksiyonlarının, Afyonkarahisar ilindeki ruminant abort vakalarında önemli rol oynadığını göstermektedir.

Pestiviruses are important viral agents that can cause abortion in ruminants. In this study, roles of Border Disease Virus (BDV) and Bovine Viral Diarrhoea Virus (BVDV) were investigated in ruminant abortion cases. Aborted foetal tissue samples were collected from 101 animals (74 sheep foetuses and 27 bovine foetuses), each from epidemiologically different farms, during the months of January 2016 and December 2017 in the Afyonkarahisar Province. One step real-time duplex RT-PCR was used for the detection of BDV and BVDV RNA. Genetic characterization of the field isolates of pestiviruses was conducted by sequencing 5' untranslated region (5' UTR). BDV RNA was detected in 9 (12.16%) of the 74 aborted sheep foetuses, whereas BVDV RNA was detected in 6 (22.2%) of the 27 bovine foetuses. Phylogenetic analysis based on the 5' UTR region indicated that BDV isolates in the present study belong to BDV-7 genotype whereas BVDV isolates belong to BVDV-1 genotype. The results of this study showed that pestivirus infections play important role in ruminant abortion cases in Afyonkarahisar province.
The role of pestiviruses (BDV and BVDV) in ruminant abortion cases in the Afyonkarahisar province
Keywords: Border Disease Virus; Sığır; Abort; Koyun; Bovine Viral Diarrhoea Virus; Border Disease Virus; Bovine Viral Diarrhoea Virus; Abortion; Sheep; Cattle